Acute High-Intensity Interval Exercise-Induced Redox Signaling Is Associated with Enhanced Insulin Sensitivity in Obese Middle-Aged Men - Parker, Lewan; Stepto, Nigel K.; Shaw, Christopher S.; Serpiello, Fabio R.; Anderson, Mitchell; Hare, David L.; Levinger, Itamar (Frontiers in Physiology, 2016)
Background. Obesity and ageing are associated with increased oxidative stress, activation of stress and mitogen activated protein kinases (SAPK), and the development of insulin resistance and metabolic disease. In contrast, acute exercise also increases oxidative stress and SAPK signaling, yet is reported to enhance insulin sensitivity and reduce the risk of metabolic disease. This study explored this paradox by investigating the effect of a single session of high-intensity interval-exercise (HIIE) on redox status, muscle SAPK and insulin protein signaling in eleven middle-aged obese men. Methods. Participants completed a 2 hour hyperinsulinaemic-euglycaemic clamp at rest, and 60 minutes after HIIE (4x4 mins at 95% HRpeak; 2 min recovery periods), separated by 1-3 weeks. Results. Irrespective of exercise-induced changes to redox status, insulin stimulation both at rest and after HIIE similarly increased plasma superoxide dismutase activity, plasma catalase activity, and skeletal muscle 4-HNE; and significantly decreased plasma TBARS and hydrogen peroxide. The SAPK signaling pathways of p38 MAPK, NF-κB p65, and JNK, and the distal insulin signaling protein AS160Ser588, were activated with insulin stimulation at rest and to a greater extent with insulin stimulation after a prior bout of HIIE. Higher insulin sensitivity after HIIE was associated with higher insulin-stimulated SAPK phosphorylation (JNK, p38 MAPK and NF-κB) and SOD activity (p<0.05). Conclusion. These findings support a role for redox homeostasis and SAPK signaling in insulin-stimulated glucose uptake which may contribute to the enhancement of insulin sensitivity in obese men 3 hours after HIIE.